Living Without Temporal Cues: A Case Study - Bonmati-Carrion, Maria-Angeles; Revell, Victoria L.; Cook, Tom J.; Welch, Thomas R. E.; Rol, Maria-Angeles; Skene, Debra J.; Madrid, Juan Antonio (Frontiers in Physiology, 2020)
Isolation from external time cues allows endogenous circadian rhythmicity to be demonstrated. In this study, also filmed as a television documentary, we assessed rhythmic changes in a healthy man time isolated in a bunker for nine days/nights. During this period the lighting conditions were varied between: 1) self-selected light/dark cycle, 2) constant dim light, and 3) light/dark cycle with early wake up. A range of variables was assessed and related to the sleep-wake cycle, psychomotor and physical performance and clock-time estimation. This case study using modern non-invasive monitoring techniques emphasises how different physiological circadian rhythms persist in temporal isolation under constant dim light conditions with different waveforms, free-running with a period (τ) between 24 and 25 h. In addition, a significant correlation between time estimation and mid-sleep time, a proxy for circadian phase, was demonstrated.